Plant-derived functional components: prevent from various disorders by regulating the endocrine glands. Issue 1 (31st December 2022) - Khalid, Waseem; Maqbool, Zahra; Arshad, Muhammad Sajid; Kousar, Safura; Akram, Ramish; Siddeeg, Azhari; Ali, Anwar; Qin, Hong; Aziz, Afifa; Saeed, Ayesha; Rahim, Muhammad Abdul; Zubair Khalid, Muhammad; et al.
ABSTRACT: The current review is informed about the effectiveness of plant-derived functional components that aids in the regulation and health of endocrine glands. The endocrine glands include the thyroid, adrenal, hypothalamus, pituitary and pineal, ovaries and testes that play vital functions in our body such as growth and development, metabolism, mood and reproduction controlled by hormones. The abnormalities in the functions of endocrine glands are formed various disorders, some major disorders are diabetes, goiter, kidney problem, brain-related diseases and PCOS. Different parts of plant-based foods (fruits, vegetables, cereals, beans, legumes, herbs and spices) are composed of vitamins, minerals, antioxidants and phenolic compounds that help support different body functions. It is concluded that plant-based foods are a rich source of functional components that play a valuable role in regulating the function of the endocrine glands.